An Analysis of Relationship of Sleep Pattern and Sleep Quality with Eating Behaviour among University Students - Ozdisli, Merve Gizem; Yildiz, Emine (Mattioli 1885, 2021)
This study was carried out to investigate the relationship between sleeping habits and quality of eating habits of students. The study was conducted on 248 (135 female, 113 male) healthy individuals, aged 18-32 years, who were educated at Hasan Kalyoncu University Health Sciences High School between November 2015 and March 2016. Individual characteristics of the individual, food consumption and nutrition habits, anthropometric measurements and physical activities were questioned with a questionnaire. The Pittsburgh Sleep Quality Index was used to determine the duration and quality of sleep of individuals. The mean age of women participating in the study was 20.33 +/- 2.16 years, the mean age of male subjects was 21.39 +/- 2.31 years, the mean BMI of female subjects was 22.3 +/- 3.5 kg / m(2) and the mean BMI of male subjects was 24.8 +/- 3.7 kg / m(2). The mean duration of sleep of the female subjects was found to be 7.11 +/- 1.42 hours and the mean duration of sleep of the male subjects was 7.09 +/- 1.42 hours. 38.5% of the female subjects had a Pittsburgh score of less than 5 and 5, good sleep quality, 61.5% had a Pittsburgh score of 6 or more, and poor sleep quality. 42.5% of male subjects had a Pittsburgh score of less than 5 and 5, good sleep quality, 57.5% had a Pittsburgh score of 6 or more, and poor sleep quality. The mean energy intake of female subjects on a one-day diet was 1333.30 +/- 524.19 kcal, and the mean energy intake of male subjects on a one-day diet was found to be 2010.1 +/- 824.70 kcal. There was a high statistically significant difference in energy consumption among individuals compared to gender (P = 0.001). There was a very weak significant correlation between negative fat saturated fatty acids and sleep duration (r = -0.129, P = 0.042). The mean PAL value of female subjects was 1.87 +/- 0.35, and the mean PAL value of male subjects was 1.98 +/- 0.18. There was a very high statistically significant difference between PAL values (P = 0.002). As a result, sleep duration and quality are indispensable for healthy nutrition and healthy living. It is seen that shortening the sleeping period and decreasing the sleep quality causes many health problems such as obesity, hypertension and insulin resistance. It is aimed to improve the sleep duration and quality of the students, to live a healthier life with optimal nutrition and thus to minimize the risk of diseases.
Keywords: PUKI; Sleep quality; Sleep duration; Food consumption; Physical activity; University students